Best books

Archives

Download e-book for kindle: Analisis Funcional vs. Matricial by Demetrio Stojano

By Demetrio Stojano
ff

Show description

Read or Download Analisis Funcional vs. Matricial PDF

Similar spanish books

Download e-book for iPad: The alphabet in the park : selected poems by Adélia Prado

This is often the 1st publication released in English by way of of the paintings of Brazilian poet Adélia Prado. Incorporating poems released during the last fifteen years, The Alphabet within the Park is a booklet of ardour and intelligence, wit and intuition. those are poems approximately human matters, in particular these of girls, approximately residing in one’s physique and out of it, concerning the actual but in addition the religious and the imaginitive existence.

Extra info for Analisis Funcional vs. Matricial

Example text

Ya vimos en la Ec. 26) que d (λ x , S) = |λ| d (x , S) para cualesquiera λ ∈ K y x ∈ E. Para ver la desigualdad triangular fijemos x, y ∈ E y w ∈ S. Luego x + y + S = (x + w) + y + S = ´ınf (x + w) + (y + z) ≤ x + w + ´ınf y + z . z∈S z∈S Tomando ahora ´ınfimo sobre w ∈ S nos queda que x + y + S ≤ x + S + y + S . Es sabido que ΠS es K-lineal. Como d (x , S) ≤ x (para todo x ∈ E), vemos que ΠS ≤ 1. 4. Asumamos ahora que E es completo, y sea (xn )n∈ N una sucesi´on en E tal que (xn + S)n∈N es de Cauchy en E/S.

Sean E y F dos EN’s. Dado un S E tal que n = dim S < ∞, vale que todo operador acotado T0 ∈ L(S , F ) se puede extender a un T ∈ L(E , F ). Se cumple que T |S = T0 y que T ≤ K T0 , donde la constante K ≥ 1 depende de E y de S, pero es la misma para todos los operadores T0 ∈ L(S , F ) (y todos los espacios F ). Proof. Sea P ∈ L(E) el proyector sobre S de la Prop. 11, y sea K = P . Como def R(P ) = S tiene sentido definir la composici´on T = T0 ◦ P ∈ L(E , F ). Eso es todo. 13. Sea E un EN. Usando el Cor.

Demostraci´on. Escribamos r = λ · r con λ ∈ (0, 1) y ε = 1 − λ ∈ (0, 1). Denotemos por V = T BEa . Dado y ∈ BFa (0, r), por hip´otesis existe un y1 ∈ V tal que y − y1 < ε · r , o sea que y − y1 ∈ BFa (0, ε · r) . 54 Por la Ec. 9) y la h´omeo-ness de x → ε · x, vemos que BFa (0, ε · r) = ε · BFa (0, r) ⊆ ε · V = ε · V ε · V = T ε · BEa = T (BEa (0, ε) ) . y que Luego existe un y2 ∈ ε·V tal que y−y1 −y2 < ε2 ·r. Siguiendo inductivamente, construimos una sucesi´on (yn )n∈ N en F que verifica las siguientes condiciones: yn ∈ εn−1 · V n and y− yk < εn · r n∈N.

Download PDF sample

Rated 4.92 of 5 – based on 9 votes

Comments are closed.